The Atbara porphyry gold-copper systems in the Red Sea Hills, Neoproterozoic Arabian-Nubian Shield, NE Sudan - Sasmaz, Ahmet (Elsevier, 2020)
Atbara city is located between the Nile and Atbara rivers, approximately 300 km northeast of Khartoum. The Atbara porphyry gold-copper system is situated at eastern part of Atbara about 70 km in the Red Sea Hills, Neoproterozoic Arabian-Nubian Shield, NE Sudan. The gold-copper system is observed within different colored quartz veins that fill the tectonic zones in metasomically altered felsic-acidic igneous rocks Gold mineralization in the Atbara is observed in an area of 200 km(2) and represented with pyrite, pyrrhotite, chalcopyrite, gold, galena, chalcocite-covellite, tetrahedrite-tennantite, hematite and goethite in the mineralized zone of the study area. The white and brown color quartz veins had E-W, NE-SW and NW-SE directions in these sectors and thickness between 5 and 300 cm. White color quartz samples had low concentration between 0.2 and 1.5 ppm and brown color quartz samples had high gold concentrations ranging from 1.0 to 26.63 ppm. Au does not have positive correlation with other elements, only except for Te and W. In contrast, there is no significant relationship between gold and copper in areas where copper is observed intensively. Cu has positive correlation with Bi, Cd, Pb, U, Hg and Ag. The average SREE contents in the hydrothermally altered wall rocks, copper mineralization and the quartz veins ranged from 10.2 ppm for Sector SA (SA, SB, SC, SD, SE and SF are the mining operation areas in the study area), to 14.27 ppm for Sector SB, 1.05 ppm for Sector SC, 20.89 ppm for Sector SD, 3.49 ppm for Sector SE, and 36.33 ppm for the Sector SF. The most of the studied samples have negative Ce and positive Eu anomalies with the LREE enrichment. This showed that it have low oxygen fugacity in the resource area of the hydrothermal solutions and an alkali magmatic source indicating an early stage of magmatic differentiation.
Keywords: Gold occurrence; Copper; Quartz veins; Atbara; Red Sea Hill; Sudan